2017
DOI: 10.1136/bmjdrc-2016-000326
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis as a possible early sign of diabetes mellitus

Abstract: ObjectiveThe early diagnosis of (pre)diabetes mellitus is essential for the prevention of diabetes complications. It has been suggested that gum disease (periodontitis) might be an early complication of diabetes and may be a useful risk indicator for diabetes screening. Therefore, a dental office could be a good location for screening for (pre)diabetes in patients with periodontitis using a validated glycated hemoglobin (HbA1c) dry spot analysis.Research design and methodsA total of 313 individuals from a univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 46 publications
4
62
1
3
Order By: Relevance
“…In this study, we found a strong correlation between serum 25(OH)D 3 deficiency and the severity of type 2 diabetic periodontitis. Consistent with previous reports, T2DCP patients had a more severe periodontal status along with higher serum levels of IL‐1β and TNF‐α than CP patients without diabetes. We conjectured that factors such as age, FBG, HbA1c, and the systemic inflammatory status other than calculus metabolism may influence the risk of periodontitis in diabetes in the face of VD 3 deficiency.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we found a strong correlation between serum 25(OH)D 3 deficiency and the severity of type 2 diabetic periodontitis. Consistent with previous reports, T2DCP patients had a more severe periodontal status along with higher serum levels of IL‐1β and TNF‐α than CP patients without diabetes. We conjectured that factors such as age, FBG, HbA1c, and the systemic inflammatory status other than calculus metabolism may influence the risk of periodontitis in diabetes in the face of VD 3 deficiency.…”
Section: Discussionsupporting
confidence: 92%
“…Periodontitis is a major complication of type 2 diabetes mellitus (T2DM) . Patients with type 2 diabetic periodontitis (T2DCP) often suffer from severe periodontal tissue inflammation and destruction . Although T2DM and chronic periodontitis (CP) have relatively higher incidences with age in the general population, and those that are already afflicted with one disease are more inclined to develop the other, the specific metabolic risk factors and pathological mechanisms mediating these associations have yet to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Given the suggested dose–response relationship between blood glucose level and implant complications, patients with (pre‐)diabetes should not only be advised regarding the importance of attaining and maintaining good glycaemic control both for general health, but also for the sake of preventing implant failure. Furthermore, due to the high rate of undiagnosed (pre‐)diabetes that leaves the patient unaware of his or her hyperglycaemia, it would also be prudent to be prepared to offer the patient chairside assessment that could be done by collecting blood samples and sending them to a laboratory on a weekly basis for measurement of the HbA1c from a dry blood spot (Teeuw, Kosho, Poland, Gerdes, & Loos, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although this investigation was not designed as a cross‐sectional or a population survey, it is interesting to note that the prevalence of MetS in our periodontitis population is higher than the prevalence reported previously in a cross‐sectional study in a Dutch population (Bos et al., ) and also higher than the prevalence of MetS reported in various populations in Europe (5%–27%) (Alberti et al., ). Interestingly, a recent investigation into hidden diabetes in periodontitis patients suggested that periodontitis is a possible early indicator of disturbed metabolic control (Teeuw, Kosho, Poland, Gerdes, & Loos, ). The current findings also point to the same direction and suggest that periodontitis patients may present with undiagnosed metabolic disturbances.…”
Section: Discussionmentioning
confidence: 99%